In Vitro and Preclinical Antitumor Evaluation of Doxorubicin Liposomes Coated with a Cholesterol-Based Trimeric β-D-Glucopyranosyltriazole - Aline Teixeira Maciel e Silva; Ana Luiza Chaves Maia; Juliana de Oliveira Silva; Sued Eustáquio Mendes Miranda; Talia Silva Cantini; Andre Luis Branco de Barros; Daniel Crístian Ferreira Soares; Mariana Torquato Quezado de Magalhães; Ricardo José Alves; Gilson Andrade Ramaldes (MDPI AG, 2023)
The coating of liposomes with polyethyleneglycol (PEG) has been extensively discussed over the years as a strategy for enhancing the in vivo and in vitro stability of nanostructures, including doxorubicin-loaded liposomes. However, studies have shown some important disadvantages of the PEG molecule as a long-circulation agent, including the immunogenic role of PEG, which limits its clinical use in repeated doses. In this context, hydrophilic molecules as carbohydrates have been proposed as an alternative to coating liposomes. Thus, this work studied the cytotoxicity and preclinical antitumor activity of liposomes coated with a glycosyl triazole glucose (GlcL-DOX) derivative as a potential strategy against breast cancer. The glucose-coating of liposomes enhanced the storage stability compared to PEG-coated liposomes, with the suitable retention of DOX encapsulation. The antitumor activity, using a 4T1 breast cancer mouse model, shows that GlcL-DOX controlled the tumor growth in 58.5% versus 35.3% for PEG-coated liposomes (PegL-DOX). Additionally, in the preliminary analysis of the GlcL-DOX systemic toxicity, the glucose-coating liposomes reduced the body weight loss and hepatotoxicity compared to other DOX-treated groups. Therefore, GlcL-DOX could be a promising alternative for treating breast tumors. Further studies are required to elucidate the complete GlcL-DOX safety profile.